Influenza circulating strains in Argentina exhibit differential induction of cytotoxicity and caspase-3 in vitro - Mersich, S E (2004)
Fil: Mersich, S.E. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Laboratorio de Virología. Departamento de Bioquímica; Argentina.